Strange Stories of the Great Valley: The Adventures of a Boy Pioneer - Grosvenor, Abbie Johnston, 1865-1948; Merrill, Frank T., 1848-1923 (Salt Lake City, UT : Project Gutenberg, 2015)
"Strange Stories of the Great Valley: The Adventures of a Boy Pioneer" by Johnston Grosvenor is a historical fiction novel written in the early 20th century. The book follows the adventures of a young pioneer named Obadiah "Doby" Holman as he navigates life on the American frontier during the early 19th century, blending tales of exploration, encounters with notable historical figures, and the challenges of settler life. The opening of the novel introduces readers to Doby as he joyfully skips stones along the Ohio River in 1816, showcasing his youthful spirit and curiosity. Alongside his father, he explores the beginnings of civilization in the area around Marietta, Ohio, while they prepare for their journey as pioneers. As a storm approaches, they take refuge beneath a large oak tree, which leads to a conversation about the mysterious Mound-Builders and the peculiar earthworks left behind. The chapter captures the essence of frontier life, Doby's eagerness for adventure, and his exploration of the past, setting the stage for the stories and encounters with historic figures that lie ahead in his journey. (This is an automatically generated summary.)
Release date is 2015-02-17
E-text prepared by Beth Baran and the Online Distributed Proofreading Team
Keywords: Frontier and pioneer life -- Ohio River Valley -- Juvenile fiction